Usefulness of the Czech TOP 100 companies´ codes of ethics - Pitsela, Margarita; Procházka, David Anthony; Kučera, Dušan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2022)
In today’s world, firms' actions have a tremendous impact on the development of societies. For this reason, it is crucial for firms to promote ethical behaviors and practices. Organizations commonly use codes of ethics (or codes of conduct) to fulfill this purpose. However, in many cases, the codes of ethics do not emphasize promoting ethical behavior but compliance with the laws. In this thesis, comparative content analysis is conducted on 59 codes of ethics from Czech companies based on the list Czech Top 100 to investigate whether those codes of ethics promote ethical practices and thus are useful or simply copy the law. The results of this research bring evidence that the commitment of Czech companies toward the adoption and implementation of ethical practices is minimal.
Vedoucí práce: David Anthony Procházka
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2022
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2022
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses